Developed Upgraded Method for Solving Problems of Factor Groups - B. Hamid, Abdelrahim (Gezira Journal of Engineering and Applied Sciences, 2018)
Through teaching the syllabus of the group theory, appeared some ambiguity in presentation the basic concepts of factor (quotient) groups. This is because the definitions and theorems expressed in abstract language, also the explanation examples are inadequate in most references. For this reason, and after research, the researcher has found a way to reach an upgraded developed method for understanding and solving the problems of finite and infinite factor groups.